2015
DOI: 10.1021/acs.nanolett.5b00175
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Quantification of Nanoscale Processes in Lithium Batteries by Operando Electrochemical (S)TEM

Abstract: An operando electrochemical stage for the transmission electron microscope has been configured to form a "Li battery" that is used to quantify the electrochemical processes that occur at the anode during charge/discharge cycling. Of particular importance for these observations is the identification of an image contrast reversal that originates from solid Li being less dense than the surrounding liquid electrolyte and electrode surface. This contrast allows Li to be identified from Li-containing compounds that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
250
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 283 publications
(270 citation statements)
references
References 29 publications
(35 reference statements)
8
250
0
Order By: Relevance
“…When Gu et al 63 applied the liquid-cell configuration to study a battery with a Si nanowire electrode (Figure 6a), they not only observed phenomena that are consistent with the open-cell studies but also successfully unraveled the dynamics of the electrolyte, which is difficult to probe using the open-cell setup. 64 Following this pioneering work, Zeng et al 22 observed Li metal dendritic growth and SEI layer formation (Figures 6b and c) 65 used a similar configuration to determine the lithiation state of LiFePO 4 in real time with a relatively high spatial resolution. Beyond these discoveries, the liquid-cell configuration also holds potential for further improvements.…”
Section: Liquid-cell Configurationmentioning
confidence: 99%
“…When Gu et al 63 applied the liquid-cell configuration to study a battery with a Si nanowire electrode (Figure 6a), they not only observed phenomena that are consistent with the open-cell studies but also successfully unraveled the dynamics of the electrolyte, which is difficult to probe using the open-cell setup. 64 Following this pioneering work, Zeng et al 22 observed Li metal dendritic growth and SEI layer formation (Figures 6b and c) 65 used a similar configuration to determine the lithiation state of LiFePO 4 in real time with a relatively high spatial resolution. Beyond these discoveries, the liquid-cell configuration also holds potential for further improvements.…”
Section: Liquid-cell Configurationmentioning
confidence: 99%
“…The downside to this ability to see small areas is that because the electron beam has a strong interaction with the sample, it can cause significant levels of electron beam damage. However, the last 40 years of protein crystallography and more recently the use of in-situ liquid stages to study chemical reactions in the (S)TEM [3], have shown that this beam damage effect can in most cases be mitigated by the use of extremely low-dose imaging (a dose rate of less than 0.1 electrons/angstrom 2 /s and a cumulative dose of less than 10 electrons/angstrom 2 ). In addition to simply lowering the dose through conventional means (changing the emission current and probe dwell time), more recent use of compressive sensing/in-painting methods for STEM has also been shown to lower the effective dose and dose rate [4].…”
mentioning
confidence: 99%
“…Figure 1 shows the typical field distribution around the Protochips electrochemical stage that allows the fields to be quantified and the most probable location of the reaction to be identified [2]. To make sure that the electron beam does not have any effect on the electrochemistry being performed, the electron beam dose rate is carefully calibrated to be below the electrolyte damage threshold prior to operando electrochemical cycling (in this case all experiments use a dose  0.3 electrons/Å 2 /s) [3]. As such, typical beam effects such as the formation of bubbles and/or precipitates from the breakdown of the electrolyte are completely avoided.…”
mentioning
confidence: 99%